PENGARUH DISIPLIN KERJA, MOTIVASI KERJA TERHADAP LINGKUNGAN KERJA DAN KINERJA KARYAWAN PT. SAMSONITE INDONESIA - Amirudin Amirudin (RJABM (Research Journal of Accounting and Business Management), 2021)
In achieving organizational goals, of course, employees are required to maximize the performance they have. Employee performance is an important thing for the organization to pay attention to, because it can affect the achievement of goals and the progress of the organization in the changing global competition. The objectives of this study are: 1) to analyze and determine work discipline on employee performance. 2) analyze and determine the work motivation of employees. 3) analyze and determine the work environment on employee performance. 4) analyze and determine the effect of work discipline, work motivation and work environment simultaneously on employee performance.This research method uses a survey method with a quantitative research approach. survey research is meant to explain causal relationships and hypothesis testing. the population in this research are all employees of PT. Samsonite Indonesia as many as 125 employees, using the Slovin formula, the employees of PT. The sample of Samsonite Indonesia used in this study is 96 people.The results of this study indicate that: 1) Work discipline has a positive and significant effect on the employee performance of PT Samsonite Indonesia. 2) Motivation has a positive and significant effect on the employee performance of PT Samsonite Indonesia. 3) The work environment has a positive and significant effect on the employee performance of PT Samsonite Indonesia. 4) Work discipline, work motivation and work environment simultaneously have a positive and significant effect on employee performance of PT Samsonite Indonesia employees.